Effects of glyphosate and glyphosate-based herbicide on learning and memory of the buff-tailed bumblebee (Bombus terrestris) - Kaakinen, Kimmo (WILEY, 2025)
The decline of insect pollinators is a global concern, and the use of pesticides has been identified as a potential cause for it. Glyphosate-based herbicides (GBHs) are the world's most used pesticides, but until recent years they have been claimed to be safe for non-target organisms, such as pollinators. Using controlled arena experiments, we investigated the effects on the learning and long-term memory of buff-tailed bumblebees, Bombus terrestris (L.) (Hymenoptera: Apidae), of a single field-realistic dose of glyphosate, both in its pure form and as a commercial herbicide (Roundup Gold) containing the active ingredient (a.i.) glyphosate and other co-formulants. We found that glyphosate in its pure form caused deterioration in the learning ability of bumblebees in a 10-color discrimination experiment; the glyphosate-treated bees discriminated colors over 10% worse than the untreated control bees. However, the commercially used GBH (Roundup Gold) had no observable effect on the learning ability of the bumblebees, despite the fact that this herbicide contained the same amount of glyphosate as its pure form. These findings shed light on the potential risks associated with agrochemicals previously considered safe for pollinators and emphasize the need for comprehensive risk assessments of pesticides, including evaluations of cognitive functions in pollinators. Therefore, we propose that future pesticide testing should incorporate broader assessments to ensure the safety of pollinators in agricultural landscapes.